Stimulasi Permainan Puzzle Berpengaruh terhadap Perkembangan Sosial dan Kemandirian Anak Usia Prasekolah - Tunggul Sri Agus Setyaningsih; Hesti Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to analyze the effect of providing puzzle game stimulation on social development and independence in preschool children. Method This study uses quantitative research methods with a quasi experimental one group pre-post test design. The results of the study were analyzed using the Wilcoxon test on the development status of children before and after the intervention which obtained a significant value of 0,000 (p-value <0.05). Conclusion, there is a significant influence between providing puzzle stimulation on social development and independence. Keywords: Child Development, Puzzle Games, Quasi Experimental